Repertorio Americano: intellectuals and environment (1919-1929) - Urbina Gaitán, Chester (2018)
Repertorio Americano published between 1919 and 1929 a set of writings that provide an alternative to the capitalist utilitarian view of nature perception and Environment. At a general level texts emphasize the dependence of human on nature, the need to teach on this subject in primary education, higher spiritual level that is nature - mainly tree - against human society, socialist vision that the interests of the earth are first; true democracy lies in it except that natural resources cannot be privatized because they belong to all mankind. Moreover, the nature relates to the spiritual world, and the damage that would do to nature will be returned in the destruction of the human world.